Optimalisasi Pengelolaan ZISWAF untuk Mendukung Pencapaian SDGs di Indonesia - Puji Purnawan; Nur Rahmi Irfaniah (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to examine the contribution of Zakat, Infaq, Alms, and Waqf (ZISWAF) in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia through a descriptive qualitative approach using a literature review method. ZISWAF as an instrument of Islamic philanthropy is considered to have great potential in reducing poverty, social inequality, and providing basic services in a sustainable manner. The results of the study show that although the collection of ZISWAF funds has increased, challenges remain in the form of low zakat literacy, lack of technological innovation, and uneven trust in management institutions. Case studies on productive zakat and education waqf programs show positive results on economic empowerment and increased access to education. This study emphasizes the importance of collaboration between the government, the private sector, and the community as well as strengthening governance, public education, and the adoption of digital technology as a strategic step in optimizing the role of ZISWAF in achieving the SDGs. This study makes a conceptual contribution in integrating the Islamic philanthropic approach with sustainable development strategies in Indonesia.